2017
DOI: 10.1186/s12898-017-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Fish with red fluorescent eyes forage more efficiently under dim, blue-green light conditions

Abstract: BackgroundNatural red fluorescence is particularly conspicuous in the eyes of some small, benthic, predatory fishes. Fluorescence also increases in relative efficiency with increasing depth, which has generated speculation about its possible function as a “light organ” to detect cryptic organisms under bluish light. Here we investigate whether foraging success is improved under ambient conditions that make red fluorescence stand out more, using the triplefin Tripterygion delaisi as a model system. We repeatedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Previously, we found that red fluorescent irides are most prevalent in small fish feeding on small, eyed prey [20], hinting at the possibility that light emission from the iris may constitute a visual aid in detection [21]. Indeed, one of those species captured more prey under "fluorescent-friendly" conditions in a subsequent experiment [22], even though the contribution of active photolocation to this finding remains to be shown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, we found that red fluorescent irides are most prevalent in small fish feeding on small, eyed prey [20], hinting at the possibility that light emission from the iris may constitute a visual aid in detection [21]. Indeed, one of those species captured more prey under "fluorescent-friendly" conditions in a subsequent experiment [22], even though the contribution of active photolocation to this finding remains to be shown.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, we test the hypothesis that light radiated from the iris is up-or down-regulated in response to the environmental context. Since up-and down-regulation of fluorescence is slow [18,23] and therefore hard to quantify in freemoving individuals, we focus on the ocular spark, a bright spot on the iris, just below the pupil (figure 1, [19][20][21][22][23][24]. Ocular sparks are produced by the protruding spherical lens (figure 2a) which allows downwelling light to cross without entering the pupil, a feature of most bony fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Although fluorescent pigments are widespread in benthic marine organisms (Alieva et al., ; Eyal et al., ; Marshall & Johnsen, ; Sparks et al., ), their presence in fish living in shallow water (0–40 m) has only recently been confirmed (Anthes et al, ; Gerlach et al, ; Michiels et al., ; Sparks et al., ). To date, several studies investigated potential functions of red fluorescence in fish, including intraspecific communication, camouflage, and prey detection (Anthes et al., ; Detecting the Detector; Harant & Michiels, ; Meadows et al., ). In this study, however, we only focus on assessing whether such a red signal stands out in front of natural backgrounds and thus generates a perceptible contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Anthes et al [12] also found that the presence of conspicuously red fluorescent irides seems to be associated with a micro-predatory lifestyle [5, 13]. Moreover, a recent experimental study indicated that foraging success increases under dim, “fluorescence-friendly” cyan illumination relative to broad spectral illumination at the same brightness in the triplefin Tripterygion delaisi [14].…”
Section: Introductionmentioning
confidence: 99%